Atomically Dispersed Iron with Densely Exposed Active Sites as Bifunctional Oxygen Catalysts for Zinc–Air Flow Batteries. Issue 8 (13th December 2021) - Gao, Lesen; Gao, Xia; Jiang, Peng; Zhang, Cunyin; Guo, Hui; Cheng, Yuanhui
Abstract: Atomically dispersed iron embedded carbon is a promising bifunctional catalyst for the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER), but its exposed iron sites must be increased. Herein, the authors propose a double steric hindrance strategy by using zeolitic imidazolate frameworks‐8 as the first barrier skeleton and encapsulated phenylboronic acid as the second space obstruction to realize densely exposed atomic iron sites. Prepared PA@Z8‐FeNC has the highest iron content (5.49 wt%) among reported transition‐metal‐based single‐atom oxygen catalysts. Meanwhile, its concave surfaces, hollow structures, and hierarchical pores enable the high utilization rate of iron sites to 88.5 ± 4.5% and exposed active site density to 5.2 ±  0.3 ×  10 20 sites g −1 . Resultantly, PA@Z8‐FeNC exhibits superior activity and stability to commercial Pt/C and IrO2 for the ORR and OER in half‐cells and zinc–air flow batteries. This provides insight for developing densely and accessibly active sites in single‐atom catalysts. Abstract : A double steric hindrance strategy is performed to simultaneously achieve atomic‐level dispersion of FeN moieties with the highest loading and recorded utilization rate among transition‐metal‐based single‐atom catalysts for the oxygen reduction and evolution reactions.